Cashew nut shell liquid plant design and operation a plant design - Lim, Dennis Karlo E.; Sahagun, Rene R.; Mariano, Victor B.; Baynosa, Marjorie L. (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
The world market for cashew nut well liquid (CNSL) is very promising. Current trends show that there is a large demand of CNSL from various countries like United States, China and Japan while the current production of CNSL is not sufficient. Present applications of CNSL are mainly on polymer-based industries but new applications are being explored.The Philippines is highly capable of being a major player in the emerging CNSL industry. Local production of cashew can suffice the required quantity of raw material. Unfortunately, no company in the Philippines produce CNSL. Only the kernels of the cashew are considered as profitable product making the shells waste product. These prompted this group of chemical engineering students to design a plant that , if ever erected, should tap the large CNSL industry potential of the country. Moreover, this plant can help to local cashew industries to minimize their cashew-based waste production since the main raw material of the proposed plant is the supposed-to-be-wasted cashew nut shells. The group selected the method of production based on two factors: economic feasibility and product yield. After analysis of the existing methods of production, the group decided to combine three existing methods. The first stage in the hot-oil method which will be followed by oil expression method, while the last stage involves solvent extraction method. The main raw material for the process is raw cashew nut shells. This three-stage process allows the maximum extraction of the CNSL content of the shells. Each of the stages yields CNSL product the passes that existing product specifications for untreated CNSL. The proposed plant location is strategically selected so as to optimize the transport of both raw materials and products. Roxas, Palawan has a bulk supply of raw materials, has a seaport for exporting the products, and has sufficient energy supply.Financial study shows that proposed plant has a low payback period of only 1.94 years and annual profit of Php 54,732,900.00 that is adequate for plans of plant expansion.On the whole, the proposed CNSL plant satisfies all the necessary factors for it to be worthy of investing for the construction of the plant.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Cashew; Cashew nut industry; Factories -- Design and construction